On nonlinear Schrödinger problem with amplification process - Raimondas Čiegis; Genė Kairytė; Violeta Pakalnytė (Lietuvos Matematikos Rinkinys)
In this paper we consider the nonlinear Schrödinger problem with amplification process. We define a new unknown function and derive a nonlinear equation for this function. Theoretical analysis of a symmetrical finite difference scheme is given and the convergence is proved.